Junior Worldmark encyclopedia of world holidays. Volume 4, New Year, Ramadan and Id al-Fitr, Thanksgiving and Harvest Festivals - Griffin, Robert H., 1951-; Shurgin, Ann H., 1952- (Detroit : UXL, 2000)
Provides general overviews of three holidays celebrated in thirty countries around the world, including New Year, Thanksgiving, and Harvest Festivals; and contains details on how each holiday is observed in one or more countries, discussing the history, stories, customs, clothing or costumes, food, arts and games, symbols, and music associated with each celebration.
Includes bibliographical references and index.
5-8
Keywords: Festivals -- Encyclopedias, Juvenile; Holidays -- Encyclopedias, Juvenile; Encyclopedias and dictionaries; Festivals -- Encyclopedias; Holidays -- Encyclopedias; Encyclopedias and dictionaries; Festivals -- Encyclopedias; Holidays -- Encyclopedias